'On Just Terms', Revisited. (June 2017) - Weis, Lael K
Although it is now generally accepted that s 51(xxxi) is a constitutional guarantee, it continues to be applied using characterisation analysis, the method of analysis used to apply grants of legislative power. This article argues that this is a mistake: if s 51(xxxi) is a constitutional guarantee, then it should be analysed like a constitutional guarantee. It takes to task the High Court's self-consciously comparative defence of characterisation analysis, which relies on the US Constitution's Fifth Amendment 'takings clause' as a foil. The article demonstrates that in some respects the differences between the two constitutional property clauses have been overstated, while in other respects they have been overlooked. From a broader comparative perspective, the most significant feature of s 51(xxxi) is not its use of the term 'acquisition', but its lack of reference to 'compensation' and use instead of the phrase 'on just terms'. By resituating s 51(xxxi) in comparative perspective, the analysis provided in this article makes two important contributions. First, it deepens existing jurisprudential critiques by providing a more precise diagnosis of the problem with characterisation analysis. Second, it proposes and defends an alternative approach that is responsive to that diagnosis, that is better supported by the text and structure of s 51(xxx), and that is consistent with the High Court's commitment to the thesis that s 51(xxxi) is a constitutional guarantee.